DynaMo - Software for vibration based structural health monitoring - F. Magalhães (2012)
This paper presents an innovative software for continuous dynamic monitoring of civil infrastructures. The followed approach is based in the continuous on-line automatic identification of the structure modal parameters, using its response under operation and adopting state-of-the-art identification algorithms. Therefore, the monitoring software, called DynaMo, includes routines for data and results management, algorithms for operational modal analysis, statistical tools for elimination of environmental and operational factors on the identified modal parameters and also statistical tools for automatic identification of abnormal frequency values that might be associated with the occurrence of damage. The utility and efficiency of DynaMo is illustrated with an application on a large span concrete arch bridge that is being monitored since 2007. Â(c) 2012 Taylor & Francis Group.